Forest Zoning as a Pedagogical System: Intergenerational Transmission of Ecological Knowledge in the Dukuh Indigenous Community - Romy Faisal Mustofa; Randy Fadillah Gustaman; Lilis Rosita (Universitas Negeri Padang, 2026)
Amidst global environmental change, the erosion of Traditional Ecological Knowledge (TEK) poses a critical threat to biodiversity conservation and sustainable governance. While TEK is widely recognized, the mechanisms of its intergenerational transmission, particularly how it is embedded within spatial governance, remain a significant gap in cultural ecology and Indigenous studies. This study examines how the forest zoning system of the Dukuh Indigenous community in West Java, Indonesia, functions as a pedagogical infrastructure. Using a qualitative instrumental case study design, data were collected over eight months through participant observation, in-depth interviews, and documentary analysis with customary leaders, elders, adults, and youth, followed by thematic analysis. Findings reveal that the zoning system, comprising five zones including leuweung tutupan (protected forest) and leuweung larangan (sacred forest), operates not merely as a resource management tool but as a spatial curriculum. Knowledge is transmitted through experiential learning mediated by the spatial logic of the zones, where each zone dictates distinct pedagogical encounters encoding values of restraint, reciprocity, and ecological guardianship. This mechanism, termed spatial pedagogy, differs from transmission patterns in comparable Indigenous communities by embedding normative ecological lessons within the physical act of navigating the landscape, without reliance on formal instruction. This article contributes to cultural ecology by challenging static views of environmental governance and demonstrating how spatial structures function as dynamic socio-cultural learning infrastructures. It extends scholarship on Indigenous ecological knowledge by specifying spatial pedagogy as a mechanism through which governance systems inherently reproduce the ecological ethics they are designed to enforce.